A study of ultrasound/H2O2 combined surface modification on polyglycolic acid monofilaments for acupoint catgut embedding therapy application. Issue 15 (August 2019) - Fu, Shaoju; Yang, Dongchao; Zhao, Cunyi; Zhang, Peihua
Polyglycolic acid (PGA) monofilament has been regarded as an excellent acupoint catgut embedding therapy (ACET) material because it offers numerous advantages, including easy accessibility and good forming and degradable properties. However, the poor hydrophilicity and cytocompatibility are the main disadvantages preventing it from having wider applications. In this communication, two types of PGA monofilaments were first fabricated from their polymer chips, followed by ultrasound/H2 O2 combined surface modification at 1:1 (V/V), and different ultrasound frequencies (45, 60 and 75 KHz) were explored. The modified PGA monofilaments were fully characterized with respect to structure characterizations (surface morphology, weights and diameters, Fourier transform infrared spectroscopy (FT-IR) analysis and hydrophilicity), mechanical properties (tensile property, swelling behavior and flexibility) and in vitro properties (cytotoxicity, cell attachment and cell morphology). The results showed that the PGA monofilaments after modification would become coarser, with larger weights and diameters. Samples 1-PGA 75 and 2-PGA 75 exhibited the smallest contact angles at 70.51° ± 3.27° and 62.84° ± 2.53°, respectively. The FT-IR analysis results confirmed that some polar groups emerged, promoting the hydrophilicity of PGA monofilaments. The swelling behavior of monofilaments was enhanced, while tensile and bending stiffness values slightly decreased. All the prepared samples presented no toxicity, and the cell attachment ratio (cultured for 48 h) of PGA monofilaments had been greatly improved after modification. These findings present important clinical implications in the ACET materials manufacturing process and warrant further study to develop new PGA embedding materials with outstanding clinical efficacy.